Doing Cultural History : Insights, Innovations, Impulses - Mengler, Judith; Müller-Bongard, Kristina (Mainzer Historische Kulturwissenschaften, 2018)
"Doing Cultural History" collects papers on a variety of topics. The issues addressed span from the 12th to the 21st century and include the communication of peace in written and pictorial sources, narrative structures in legal texts, masculinity and violence, and new research into Scottish medieval history as well as a comparison of religious theme parks and the perception of sorcery and false saintliness in early modern Spain.